2001
DOI: 10.1063/1.1333719
|View full text |Cite
|
Sign up to set email alerts
|

High-power electroabsorption modulator using intra-step-barrier quantum wells

Abstract: We propose an efficient high-optical-saturation-power electroabsorption modulator (EAM) using intra-step-barrier quantum wells (IQWs) incorporating a step-barrier inside the well for both the conduction and the valence bands. From the simulation, we show that in the IQW (a) the onset of the redshift of the quantum-confined Stark effect is delayed to a higher electric field; and after the onset, (b) the transition energy and the oscillator strength respond sharply to the electric field. As the screening effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…It has also been reported that the strain-compensated InGaAsP/InGaAsP [4] and InAsP/GaInP [5], which have shallow wells, improves the saturation optical power at 1.3 and 1.55 lm, respectively. Recently, the use of an asymmetric QW with a step barrier to achieve high-optical-power operation has been proposed [6,7]. The intra-step quantum well (IQW) was shown to delay the onset of the red shift of the QCSE to a higher electric field, when the electric field was applied from the well to the step barrier.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the strain-compensated InGaAsP/InGaAsP [4] and InAsP/GaInP [5], which have shallow wells, improves the saturation optical power at 1.3 and 1.55 lm, respectively. Recently, the use of an asymmetric QW with a step barrier to achieve high-optical-power operation has been proposed [6,7]. The intra-step quantum well (IQW) was shown to delay the onset of the red shift of the QCSE to a higher electric field, when the electric field was applied from the well to the step barrier.…”
Section: Introductionmentioning
confidence: 99%
“…2. The slight blue shift at low field is characteristic of IQW [2], [6]. At field 60 kV/cm, the QCSE becomes dominant and the exciton resonance is redshifted and broadened.…”
mentioning
confidence: 96%
“…For EAM with unmatched electrode, a factor of 4 is typically incorporated in (1) to account for the voltage enhancement caused by the microwave reflection. The equivalent is defined as (2) where is the slope efficiency of normalized EAM transfer curve. Thus, the higher the slope efficiency, the smaller is.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the optical power driving the analogue fibre link has been increased to achieve higher radio-frequency (RF) gain, the operation of the EAM under high optical power has been studied and designs that enable the high-optical-power operation have been suggested. By combining the diluted waveguide that absorbs much reduced optical power per unit length and the modified quantum-well design [6][7][8], an EAM has been demonstrated to handle a very high optical power up to 25 dBm ( 320 mW) [9].Under this very high optical power, however, the analogue fibre link that utilises an EAM has been shown to have saturation in RF gain owing to the photocurrent resistance inherent in the EAM device [9][10][11][12]. The photocurrent resistance R ph is given by (dI ph /dV ) 21 , where I ph is the photocurrent generated in the EAM and V is the reverse bias voltage supplied to the device.…”
mentioning
confidence: 99%